2021
DOI: 10.3389/fpls.2021.650215
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Aldehyde Dehydrogenase (BADH) vs. Flavodoxin (Fld): Two Important Genes for Enhancing Plants Stress Tolerance and Productivity

Abstract: Abiotic stresses, mainly salinity and drought, are the most important environmental threats that constrain worldwide food security by hampering plant growth and productivity. Plants cope with the adverse effects of these stresses by implementing a series of morpho-physio-biochemical adaptation mechanisms. Accumulating effective osmo-protectants, such as proline and glycine betaine (GB), is one of the important plant stress tolerance strategies. These osmolytes can trigger plant stress tolerance mechanisms, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…The heterodimer Flv1/3 is conserved in all cyanobacteria and is responsible for oxygen photoreduction downstream of PSI in a Mehler-like reaction that does not produce ROS (Allahverdiyeva et al, 2013), whereas the heterodimer Flv2/4 is only present in β-cyanobacteria and was reported to be involved in photoprotection of both PSII and PSI (Zhang et al, 2009(Zhang et al, , 2012Bersanini et al, 2014Bersanini et al, , 2017Chukhutsina et al, 2015;Santana-Sanchez et al, 2019). In angiosperms, in which FDPs are absent, introduction of two FDPs could therefore possibly replace Tognetti et al, 2006Tognetti et al, , 2007aTognetti et al, , 2007bZurbriggen et al, 2008;Shvaleva et al, 2009;Coba de la Peña et al 2010;Giró et al, 2011;Ceccoli et al, 2012;Lodeyro et al, 2012;Gharechahi et al, 2015;Mayta et al, 2018;Gómez et al, 2020;Niazian et al, 2021 Overexpression of cyanobacterial and moss FDPs AET Arabidopsis, tobacco, barley, rice Yes Drought/ fluctuating light stress Yamamoto et al, 2016;Gómez et al, 2018;Wada et al, 2018;Tula et al, 2020;Shahinnia et al, 2021;Vicino et al, 2021 Abbreviations: AET, alternative electron transfer; ATP, adenosine triphosphate; LHC, light-harvesting complex; NPQ, nonphotochemical quenching.…”
Section: Increasing Electron Transport Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The heterodimer Flv1/3 is conserved in all cyanobacteria and is responsible for oxygen photoreduction downstream of PSI in a Mehler-like reaction that does not produce ROS (Allahverdiyeva et al, 2013), whereas the heterodimer Flv2/4 is only present in β-cyanobacteria and was reported to be involved in photoprotection of both PSII and PSI (Zhang et al, 2009(Zhang et al, , 2012Bersanini et al, 2014Bersanini et al, , 2017Chukhutsina et al, 2015;Santana-Sanchez et al, 2019). In angiosperms, in which FDPs are absent, introduction of two FDPs could therefore possibly replace Tognetti et al, 2006Tognetti et al, , 2007aTognetti et al, , 2007bZurbriggen et al, 2008;Shvaleva et al, 2009;Coba de la Peña et al 2010;Giró et al, 2011;Ceccoli et al, 2012;Lodeyro et al, 2012;Gharechahi et al, 2015;Mayta et al, 2018;Gómez et al, 2020;Niazian et al, 2021 Overexpression of cyanobacterial and moss FDPs AET Arabidopsis, tobacco, barley, rice Yes Drought/ fluctuating light stress Yamamoto et al, 2016;Gómez et al, 2018;Wada et al, 2018;Tula et al, 2020;Shahinnia et al, 2021;Vicino et al, 2021 Abbreviations: AET, alternative electron transfer; ATP, adenosine triphosphate; LHC, light-harvesting complex; NPQ, nonphotochemical quenching.…”
Section: Increasing Electron Transport Capacitymentioning
confidence: 99%
“…In the past 15 years, many studies on the expression of a cyanobacterial flavodoxin in plants have been published. Most of these studies reported on enhanced tolerance of transgenic plants to different environmental stresses, particularly iron deficiency and oxidative stress, under which Fd levels would normally decrease but can now be compensated for by flavodoxin expression (Tognetti et al, 2006(Tognetti et al, , 2007a(Tognetti et al, , 2007bZurbriggen et al, 2008;Shvaleva et al, 2009;Coba de la Peña et al, 2010;Ceccoli et al, 2012;Lodeyro et al, 2012;Gharechahi et al, 2015;Mayta et al, 2018;Gómez et al, 2020;Niazian et al, 2021). It was also shown that flavodoxin could functionally replace Fd in plants (Blanco et al, 2011) and additional expression of a cyanobacterial FNR could increase oxidative stress tolerance even more (Giró et al, 2011).…”
Section: Increasing Electron Transport Capacitymentioning
confidence: 99%
“…Glycine, serine and threonine metabolism play a crucial role in salt tolerance [ 48 ]. Betaine aldehyde dehydrogenase is an important gene involved in glycine betaine biosynthesis pathway, and its introduction can enhance the tolerance of plant to various abiotic stresses [ 49 ]. In this study, the regulation of DEPs and DAMs in this pathway was different in the two genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most of the salt response genes, e.g., BADH4 (betaine aldehyde dehydrogenase 4) and SKD1 (suppressor of K + transport growth defect 1, encoding for salt-induced AAA-Type ATPase), were upregulated with increasing NaCl concentration. BADH is multifunctional and can increase salt tolerance by protecting the photosynthetic apparatus (Niazian et al, 2021 ). Salinity stress activates the SKD1 expression of halophytes in the regulation of ion transporters to avoid ion toxicity; whereas reduced SKD1 expression renders Arabidopsis more salt-sensitive (Jou et al, 2004 , 2013 ).…”
Section: Discussionmentioning
confidence: 99%